The life of John Maynard Keynes - Harrod, Roy F. (London : Macmillan, 1951)
This volume by Roy Harrod is the official biography of John Maynard Keynes because it was written at the suggestion of Keynes' family, whose members co-operated fully in making available papers and letters, many excerpts from which are published for the first time. The main purpose of the biography is to make available the materials which are necessary for correct understanding and interpretation of Keynes' work. Keynes' theories and related practical proposals were influenced by his general philosophy, which took shape in his early years.
Includes bibliographical footnotes and index.
lje 22/01/2019
Loans
Keywords: Keynes, John Maynard; Economic history